FEATURES OF INTERROGATING PRISONERS OF WAR: DOMESTIC AND INTERNATIONAL EXPERIENCE - Panova, Oksana; Petrova, Valeria (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The purpose of the article is to determine the features of interrogation of prisoners of war, taking into account domestic and international experience, and to conduct a comparative analysis by comparing procedural aspects. Research methods: a comprehensive analysis of regulatory legal acts, scientific literature, and the practice of applying domestic legislation and foreign legislation was used, including empirical experience in applying the interrogation procedure in Ukraine during martial law. Results: it is substantiated that the effectiveness of interrogation is based not on physical pressure, but on a combination of psychological training, cultural awareness, and technical support. Ukraine, which already has a positive image in respecting the rights of prisoners, can use these approaches to further improve its own practice. It is noted that, taking into account the conduct of active hostilities throughout the territory of Ukraine, the processes of improving the interrogation procedures of prisoners of war face a number of objective and subjective challenges, such as: limited technical resources, insufficient specialization of personnel, information and psychological warfare. It was determined that Ukrainian practice has a number of strengths, such as: rapid adaptation to the conditions of modern warfare; active cooperation with the International Committee of the Red Cross; strict adherence to the principle of prohibition of torture and ill-treatment; recording the interrogation process as an evidentiary basis. Discussion: further development of the Ukrainian system of interrogation of prisoners of war should be based on the modernization of the technical base and the introduction of artificial intelligence systems, the creation of highly specialized HUMINT units, the expansion of international cooperation, ensuring transparency and monitoring compliance with humanitarian standards.